Wear and Water Absorption Behaviour of Banana and Sisal Hybrid Fiber Polymer Composites - V Badyankal, Pramod; T S, Manjunatha; B Veggar, Gurushanth (International Journal of Engineering and Technology, 2018)
Natural fibers are available naturally from geological, animals and plants. The composite materials can be produced by using these fibers for good properties. In this present work the hybridization of randomly oriented Banana [B] and Sisal [S] of proper composition 20%B 30%S, 30%B 20%S and 25%B 25 %S using 50% Epoxy L-12 resin with the hardener K6 in the 10:1 ratio under cold process method was used. According to ASTM G99 specimens are used to calculate the specific wear rate by pin on disc method and using Taguchi technique. The test specimen with 12 X 12 X 40 mm3 was used to calculate the percentage of water absorption.Â